Soft tissue profile changes during treatment of patients with class II malocclusion - Milutinović Jovana; Stamenković Zorana; Zelić Ksenija; Marinković Nemanja; Nedeljković Nenad (Srpski Arhiv za Celokupno Lekarstvo, 2022)
Introduction/Objective. The class II malocclusion results in disbalanced facial harmony, primarily noticeable in the profile and the lower facial third. Aside from skeletal evaluation, orthodontic diagnosis and treatment planning should include facial soft tissue analysis. The aim of the study was to identify the soft tissue profile outcomes of orthodontic treatment of class II, division 1 malocclusion patients and to determine if these changes are related to different treatment protocols. Methods. The first group was the non-extraction group (25 patients) initially treated with the Herbst appliance, and the second group was four premolars extraction group (25 patients) treated with a multibracket appliance. The patients’ cephalograms and pre- and post-treatment profile photographs were used. Results. The improvement in the non-extraction group was evident in the decrease of the nasomental angle, the angle representing the projection of the upper lip to the chin, as well as the upper lip angle. In the extraction group, the nasolabial angle showed a significant increase. Soft tissue variables showed significant differences between the groups: the total facial angle or facial convexity including the nose and the angle presenting the projection of the upper lip to the chin. Conclusion. The patients treated without extractions showed a significant improvement of the convex profile and favorable soft tissue changes in the lower third of the face.